2016
DOI: 10.1038/srep33792
|View full text |Cite
|
Sign up to set email alerts
|

Mislocalisation of BEST1 in iPSC-derived retinal pigment epithelial cells from a family with autosomal dominant vitreoretinochoroidopathy (ADVIRC)

Abstract: Autosomal dominant vitreoretinochoroidopathy (ADVIRC) is a rare, early-onset retinal dystrophy characterised by distinct bands of circumferential pigmentary degeneration in the peripheral retina and developmental eye defects. ADVIRC is caused by mutations in the Bestrophin1 (BEST1) gene, which encodes a transmembrane protein thought to function as an ion channel in the basolateral membrane of retinal pigment epithelial (RPE) cells. Previous studies suggest that the distinct ADVIRC phenotype results from altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 51 publications
4
27
0
Order By: Relevance
“…For the first time, this study provides data on the effect of ADVIRC-associated mutation BEST1-V86M on BEST1 localization, protein expression and anion transport function. While localization of mutated BEST1 to the basolateral plasma membrane was established in our study in two independent patient cell lines well in agreement with results from overexpression studies in a MDCKII cell model [18], ADVIRC-associated mutation (c.704T>C; p.(V235A)) was previously reported to be mislocalized at least in part to the apical surface of hiPSC-RPEs from an ADVIRC patient [35]. These contradictory results could suggest that proper BEST1 localization or a failure to correctly traffic to the cell membrane is rather mutation-dependent than an ADVIRC-specific characteristic and further underscores the necessity to model additional ADVIRC mutations on the basis of the hiPSC-RPE cell culture model.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For the first time, this study provides data on the effect of ADVIRC-associated mutation BEST1-V86M on BEST1 localization, protein expression and anion transport function. While localization of mutated BEST1 to the basolateral plasma membrane was established in our study in two independent patient cell lines well in agreement with results from overexpression studies in a MDCKII cell model [18], ADVIRC-associated mutation (c.704T>C; p.(V235A)) was previously reported to be mislocalized at least in part to the apical surface of hiPSC-RPEs from an ADVIRC patient [35]. These contradictory results could suggest that proper BEST1 localization or a failure to correctly traffic to the cell membrane is rather mutation-dependent than an ADVIRC-specific characteristic and further underscores the necessity to model additional ADVIRC mutations on the basis of the hiPSC-RPE cell culture model.…”
Section: Discussionsupporting
confidence: 90%
“…To analyze splicing effects of ADVIRC mutation p.(V86M) under more native conditions, PCR amplification of full-length BEST1 from hiPSC-RPE cDNA from control and the two ADVIRC patients revealed exclusively the correct amplicon of 1.7 kb indicating normal splicing of exon 4 (Supplementary Figure S3B). Sanger sequencing of the amplicon confirmed its homology to the correct BEST1 transcript, thereby supporting previous findings [35]. Next, we quantified BEST1 protein expression in whole-cell lysates of hiPSC-RPEs from control, BD, ADVIRC, and ARB genotypes by Western blot analysis.…”
Section: Localization Rna and Protein Expression Of Mutant Best1 Insupporting
confidence: 84%
“…No. 08‐0027) as previously described by Carter et al . BJ iPSC cells were maintained in TeSR‐E8 (StemCell Technologies, Cambridge, U.K.) and grown on Matrigel (Corning, St David's Park, U.K.)‐coated six‐well plates.…”
Section: Methodsmentioning
confidence: 99%
“…Best1 Q238R , another mutant associated with BVMD, was similarly reported to be mislocalized in iPSC-RPE (Milenkovic et al, 2015). A recent study by Carter et al analyzed Best1 localization in iPSC-RPE derived from a patient with ADVIRC and the associated BEST1 mutation V235A (Carter et al, 2016). …”
Section: Pathogenesis Of the Bestrophinopathiesmentioning
confidence: 99%
“…While Best1 V235A was found to be properly localized in MDCK cells (Johnson et al, 2014), Best1 was found to be mislocalized in these ADVIRC iPSC-RPE (Carter et al, 2016). This is further evidence that future trafficking studies should strive to analyze Best1 localization in a human RPE model (e.g., iPSC-RPE, fhRPE, or RPE in situ).…”
Section: Pathogenesis Of the Bestrophinopathiesmentioning
confidence: 99%